ECO-HARMONY: AN ANSWER TO ECOLOGICAL CONSCIOUSNESS - Inchody, Oliver (Journal of Dharma, 1993)
On the occasion of the World Day of Peace, January 1 990, Pope John Paul I l delivered a message on ecoloqical ethics which may provide one of the first systematic treatments of the subject in pontifical teaching: "Peace with God and Creator, peace with all Creation "i . Indeed the message starts by linking the issues of respect for nature and of harmony. "In our day, there is a growing awareness that world peace is threatened not only by the arms race, regional conflicts and continued injustices among peoples and nations, but also by a lack of due respect for nature, by the plundering of natural resources and by a progressive decline in the quality of life"